Collective Agreement for Members of Slovenian Armed Forces: Reflections on Features of Collective Negotiations in the Public Sector for the Military Profession - Ljubo Štampar (Central European Public Administration Review)
In the Republic of Slovenia, the military is an organization that, like elsewhere in the European Union (EU), belongs to the public sector. The military service is a part of the public service sector and treated with a single collective agreement for the public sector. Despite certain theses (Janowitz 1977, Moskos 1986, Callaghan and Kernic 2003, Garb 2008) about the growing similarity of the military profession with professions in the public sector or other civilian occupations, work in the military is unique because of the specific role of the military in society. However, the military profession has sufficient similarities with other public sector professions in peacetime circumstances, so that soldiers should be granted the right to bargain the economic conditions of their employment. Through the process of collective bargaining, either within the public sector or individually, they could ensure compensation for the restrictions and requirements contained in the work of soldiers. The most important European institutions, in terms of safety and protection of the rights in the European region, are following the trend of changes in the security environment, new tasks of the military organization, the changed nature of the military profession in the postmodern era, and defend the concept of the “citizen in uniform”. Through resolutions, recommendations and memorandums, they are following the trend of increasing demands for the equalization of the rights of soldiers with the rights of other citizens. In particular, the right of unions to organize and the right for the possibilities to negotiate conditions of employment are emphasized. In the EU, there are two approaches regarding the possibility of bargaining on the economic conditions of employment for soldiers. Both provide the possibility of obtaining a special allowance for soldiers serving the country.